A procedure to fully control and trace the weld quality for laser-arc hybrid welding under production conditions. (1st January 2014) - Kaplan, Alexander F.H.; Frostevarg, Jan; Powell, John
Hybrid welding combining a laser beam with a MIG/MAG-arc has high potential to fill joint gaps and to shape the weld surface. The geometrical variations and the oxidation of the joint edges can have significant influence on the resulting weld surface shape and on fatigue life. In the presented study, edge tolerances such as edge mismatch were measured. By consequent scanning of the tolerances, high speed imaging of the melt pool flow dynamics and scanning of the resulting weld surface profile, a systematic identification and explanation of the weld quality on the joint edge conditions can be achieved, even for complex products in rough industrial environment. A corresponding general procedure is presented. From a case study, the limits of quality aspects such as undercuts were quantitatively identified and qualitatively explained.